2012
DOI: 10.1007/s10714-012-1351-6
|View full text |Cite
|
Sign up to set email alerts
|

Geometrothermodynamics of five dimensional black holes in Einstein–Gauss–Bonnet theory

Abstract: We investigate the thermodynamic properties of 5D static and spherically symmetric black holes in (i) Einstein-Maxwell-Gauss-Bonnet theory, (ii) EinsteinMaxwell-Gauss-Bonnet theory with negative cosmological constant, and in (iii) Einstein-Yang-Mills-Gauss-Bonnet theory. To formulate the thermodynamics of these black holes we use the Bekenstein-Hawking entropy relation and, alternatively, a modified entropy formula which follows from the first law of thermodynamics of black holes. The results of both approache… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…This is an additional degree of freedom that can be used to reach diverse objectives. For instance, in the study of the thermodynamics of black holes [12], we found that the curvature singularities determine the phase transition structure and, in addition, Λ can be chosen in such a way that the limiting case of extremal black holes corresponds to curvature singularities too. Here, we have found that Λ can also be used to reach representation invariance directly from the phase space.…”
Section: Discussionmentioning
confidence: 99%
“…This is an additional degree of freedom that can be used to reach diverse objectives. For instance, in the study of the thermodynamics of black holes [12], we found that the curvature singularities determine the phase transition structure and, in addition, Λ can be chosen in such a way that the limiting case of extremal black holes corresponds to curvature singularities too. Here, we have found that Λ can also be used to reach representation invariance directly from the phase space.…”
Section: Discussionmentioning
confidence: 99%
“…To put it differently, black hole entropy is a dynamical quantity (which depends on the field equations), unlike its temperature which is kinematical [61][62][63]. Two examples of modified gravity in which black hole entropy takes a different form (S = A/4) are f (R) gravity [64][65][66][67][68] and the Einstein-Gauss-Bonnet gravity [69][70][71].…”
Section: Extensions Beyond General Relativitymentioning
confidence: 99%
“…Unfortunately, it is not possible to express S and Q in terms of T and φ so that the Gibbs potential cannot be written explicitly. However, in the limiting case of a vanishing cosmological constant, it is possible to find explicitly the Gibbs potential and, as shown in [38], the corresponding thermodynamic metric can be computed and the invariance with respect to the total Legendre transformation can be shown at the level of the scalar curvature.…”
Section: Geometrothermodynamic Analysismentioning
confidence: 99%
“…shown in [38], the corresponding thermodynamic metric can be computed and the invariance with respect to the total Legendre transformation can be shown at the level of the scalar curvature.…”
Section: Geometrothermodynamic Analysismentioning
confidence: 99%